Glasgow climate pact: a step on the way towards a lower carbon dioxide world. Issue 1 (February 2022) - Hammond, Geoffrey; Newborough, Marcus
Abstract : Geoffrey Hammond at the University of Bath and Marcus Newborough of ITM Power review what happened at the UN climate change conference in Glasgow last year, and what the resulting 'Glasgow climate pact' means for global warming and climate change.